2022
DOI: 10.1088/1742-6596/2193/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of copper nanoparticles using methanol extract of sugar-apple leaves (Anonnaceae squamosa), and its antioxidant activity

Abstract: Study on the biosynthesis of copper nanoparticles has been carried out employing the green synthesis method using methanol extract of Sugar-Apple leaf (Anonnaceae squamosa) as a reducing agent and stabilizer. The results of the reduction reaction of Cu2+ ions were confirmed using a UV-Vis Spectrophotometer, Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM). The results of the characterization analysis showed that the nanoparticles formed were Cu, CuO2, Cu2O, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The broadened shape of the O-H peak may result from overlap with stretching vibrations of C-H bonds at 2,890 and 2,656 cm -1 , contributing to reduced intensity in the C-H group. This broadening might also come from interactions between O-H groups in organic compounds from the organic extract and Cu + ions, impacting the overall vibrational pattern ( Maulana et al, 2022 ). The presence of atmospheric CO 2 during measurement is shown as peak at 2,120 cm -1 associated with CO 2 stretching vibrations ( Kumar et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The broadened shape of the O-H peak may result from overlap with stretching vibrations of C-H bonds at 2,890 and 2,656 cm -1 , contributing to reduced intensity in the C-H group. This broadening might also come from interactions between O-H groups in organic compounds from the organic extract and Cu + ions, impacting the overall vibrational pattern ( Maulana et al, 2022 ). The presence of atmospheric CO 2 during measurement is shown as peak at 2,120 cm -1 associated with CO 2 stretching vibrations ( Kumar et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of atmospheric CO 2 during measurement is shown as peak at 2,120 cm -1 associated with CO 2 stretching vibrations ( Kumar et al, 2018 ). Furthermore, the peaks at 1,608 cm -1 and 1,512 cm -1 correspond to stretching vibrations of C=C and C=O bonds in the ketone (C=O) group, respectively ( Maulana et al, 2022 ). The peak at 1,034 cm -1 is attributed to the C-O stretching vibrations ( Dou et al, 2021 ), and the bending modes of vibration for C-H bonds are indicated by the peak at 685 cm -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Cu NPs. The stem bark of Annona squamosa L. was utilized to synthesized 13.7 AE 3.3 nm Cu NPs, evaluated for antibacterial activity and reported inhibition zones were 12.3, 13.9, 15.7 mm against C. albicans, E. coli, and S. aureus, respectively [162]. In another report, Cu NPs were synthesized by using stem extract of Hippophae rhamnoides L. (Himalayan plant).…”
Section: Co Npsmentioning
confidence: 99%